Hubungan antara Asupan Natrium, Kalium, Aktivitas Fisik dengan Hipertensi pada Perempuan Usia diatas 45 Tahun - Yaya Zanuba Maulidya; Umu Qonitun; Idcha Kusma Ristanti (Yayasan Literasi Sains Indonesia, 2024)
High blood pressure (hypertension) is a condition in which a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality. The research design uses observational analytics with the